Synthesis and study of strontium ferromolybdate nanopowders with high degree of superstructural ordering for spintronics - M. V. Yarmolich; N. A. Kalanda; S. E. Demyanov; M. V. Silibin; G. G. Gorokh (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
The metal oxide compounds Sr2FeMoO6-δ systems with an ordered double perovskite structure due to their unique and extremely important magnetotransport and magnetic properties are among the most promising materials for spintronic devices. In the present work, we investigated the correlation between the citrate-gel synthesis conditions (pH of initial solutions and annealing temperature) and the microstructure, phase transformations and magnetic properties of the Sr2FeMoO6-δ nanopowders. According to the results, the average grain size of the powders in the dispersion grows from 250 to 550 nm with increasing of pH values. Single-phase nanosized Sr2FeMoO6-δ powders had various degrees of superstructural ordering of Fe3+ and Mo5+ (P = 65% for pH = 4, P = 51% for pH = 6 and P = 20 % for pH = 9). With increasing of pH, the Fe2+ concentration increases from 63% to 72%, and the Fe+3 concentration drops from 37% to 28%. According to the results of investigations of magnetization temperature dependence in Sr2FeMoO6-δ powders, a metastable superparamagnetic state was established at TS<19 K in low-dimensional grains. An optimized synthesis procedure, based on an initial solution of pH = 4, has allowed obtaining a single-phase Sr2FeMoO6-δ compound having grain size in the range of 50 – 120 nm and a superstructural ordering of iron and molybdenum cations of 88%. The optimum conditions of synthesis of nanopowders strontium ferromolybdate allow for the directional change of the phase composition of the synthesized nanosized ceramic with reproducible physical and chemical properties.